Determinants Of Traffic Effectiveness From E-Commerce In Indonesia Before And During The Pandemic - Ignatius Roni Setyawan; Agustin Ekadjaja; Margarita Ekadjaja; Wilson Wijaya (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2023)
This study studies the determining factor for the effectiveness of e-commerce traffic in Indonesia. Four factors influence the level of effectiveness of e-commerce traffic. The first two factors are App Store and Play Store rankings. The next factor is the number of interactions with social media users, such as Twitter, Facebook, and Instagram. The last factor determining the effectiveness of e-commerce traffic is the number of employees from each e-commerce company. Using panel data regression, this study has obtained that the Play Store rank has a more significant effect on the effectiveness of e-commerce traffic than the App Store rank. The other findings are that social media visitors do not affect significantly, while the number of employees has a positive relationship and significantly influences the effectiveness of traffic e-commerce.